Experimental validation of a Rayleigh backscattering based distributed fibre optical measurement system's thermo-elastic deformation measurement capabilities - Capobianco, Luigi (2016)
Structural Health monitoring (SHM) is nowadays a quite promising approach to gather real-time information concerning several properties of a structure and of the operational environment surrounding it. Within this discipline, fibre optics are gaining attention due to some very interesting characteristics of these devices. Being lightweight, small, flexible, embeddable, immune to electric and magnetic fields, Fibre Optic Sensors are an appealing solution for continuously assessing structural health conditions in order to prevent costly repair and to possibly avoid failures. Furthermore, in recent times, the possibility of creating a truly distributed sensor using optical fibres is attracting a considerable and increasing attentions from several different industrial fields. This work focused on a Rayleigh backscattering Distributed Fibre Optic Sensor system and on the comparison of it with more commonly used and widespread measuring equipment, as strain gages, thermocouples, photogrammetry and 3D image measurements, in order to properly understand this system's behaviour and to evaluate its accuracy. Tests have been performed to assess both strain and temperature measurement capabilities, with an increasing level of experimental complexity. The Fibre Optic Sensor worked properly and to a considerable level of accuracy was achieved in the defined testing range. It has been found of fundamental importance, in order to obtain accurate results, to properly design and select the adhesive layer bonding the optical fibre to the host structure as well as the additional coating required for temperature measurements. Heat properties of the compound surrounding the fibre have a considerable influence on temperature measurements, while viscoelastic behaviours of the selected adhesive affect the sensor's strain readings.